The Role of Filipino, Sebuano and the Mindanao Languages in the Liberation and Unification of Mindanao - Cagas-dela Cruz, Luzviminda (The Archive; Vol 14 (1998): Publication Fourteen: Wika at Pagpapalaya, 2025)
The Role of Filipino, Sebuano and the Mindanao Languages in the Liberation and Unification of Mindanao